High‐frequency resonance suppression of high‐speed railways in China. Issue 2 (1st June 2016) - Cui, Hengbin; Song, Wensheng; Ge, Xinglai; Feng, Xiaoyun
Abstract : High‐frequency resonances occur frequently in traction power supply systems of high‐speed railways in China. In this study, the autotransformer‐fed traction power supply system for a high‐speed railway was first described, and then the high‐frequency resonance mechanism was analysed. On the basis of this, the input impedance at the train's pantograph was applied to identify the resonant frequencies, and a second‐order high‐pass filter was designed by solving the minimum total input impedance with the steepest descent method. The designed filter can not only suppress the existing resonance, but also avoid a new resonance occurrence. Finally, the resonance mechanism analysis and the designed filter are verified by investigating the harmonic spectrum of the pantograph voltage in a MATLAB/Simulink‐based co‐simulation.